Humoral Theory Of Aging: A Narrative Review - Alam Ansari, Md Khursid; Rahman, Azizur; Ansari, Abid Ali; Ali, Sadique (Journal of Neonatal Surgery, 2025)
The phenotypic appearance of aging is easy to recognize, but the mechanism of aging is complex and ill-understood. Several attempts have been made to unravel the mystery of aging, but the search for a universally accepted general theory of aging is still ongoing. Aging is the inevitable, irreversible, continuous process that results in deterioration of organs, leads to functional impairment, decreases the ability to adapt to the environment, and responds to challenges to maintain homeostasis, ultimately causing death. In the elderly, phenotypic manifestation is the result of a sequence of changes that takes place at the cellular, molecular, tissue, and organ levels. According to the principle of Unani medicine, the entire universe, including the human body, is built of four basic constituents, fire, air, earth, and water, called arka̅n (elements). Each of the arka̅n has its specific qualities and properties. During the formation of a compound by intermixing of the basic constituents (arka̅n), the mutual interaction among the four contrary primary qualities of arka̅n generates a specific quality in the compound, which is uniform throughout, called the temperament of that compound/ body. As the interaction of arka̅n in the compound is an incessant process, it causes refashioning in temperament throughout the ages. The temperament of adulthood is hārr raṭb (hot-moist), which is regarded as mu‘tadil (equipoise or moderate); with advance in age, the body temperament shifts towards cold-dry. The temperament of the elderly is cold-dry, which causes structural deformity, decline in vigor, and intellectual power.